2017
DOI: 10.3892/mmr.2017.6530
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study identifying a potential plasma biomarker for determining EGFR mutations in exons 19 or 21 in lung cancer patients

Abstract: The most common type of lung cancer is non-small cell lung cancer (NSCLC), which is frequently characterized by a mutation in the epidermal growth factor receptor (EGFR). Determining the presence of an EGFR mutation in lung cancer is important, as it determines the type of treatment that a patients will receive. Therefore, the aim of the present study was to apply high-resolution metabolomics (HRM) using liquid chromatography-mass spectrometry to identify significant compounds in human plasma samples obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition to proteins and metabolites, RNA transcripts, DNA, or epigenetic modifications of DNA can be used as biomarkers . Metabolomics has been used for biomarker discovery in the life, plant/food, and environmental sciences. Recently developed configurations such as quadrupole time-of-flight (Q-TOF) tandem mass spectrometry in combination with liquid chromatography have improved metabolite screening by enhancing both mass resolution and mass accuracy. , Metabolomics investigations have been used to diagnose PCa numerous times; however, data in the Korean population is limited. Cho et al performed metabolic profiling of urine samples from PCa of Korean patients and observed an endogenous profile of corticosteroids even though the population was small …”
Section: Introductionmentioning
confidence: 99%
“…In addition to proteins and metabolites, RNA transcripts, DNA, or epigenetic modifications of DNA can be used as biomarkers . Metabolomics has been used for biomarker discovery in the life, plant/food, and environmental sciences. Recently developed configurations such as quadrupole time-of-flight (Q-TOF) tandem mass spectrometry in combination with liquid chromatography have improved metabolite screening by enhancing both mass resolution and mass accuracy. , Metabolomics investigations have been used to diagnose PCa numerous times; however, data in the Korean population is limited. Cho et al performed metabolic profiling of urine samples from PCa of Korean patients and observed an endogenous profile of corticosteroids even though the population was small …”
Section: Introductionmentioning
confidence: 99%
“…For example, linoleic acid can enhance severe asthma by causing airway epithelial damage. In addition, non-small-cell lung cancer is usually characterized by the mutation of the epidermal growth factor receptor (EGFR), and the level of linoleic acid tends to increase significantly in cancer patients with more EGFR [25,26]. Therefore, linoleic acid is highly correlated with intestinal and pulmonary diseases and could be a key biomarker for monitoring the occurrence of pulmonary and intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the model group, XHW plus anlotinib significantly reduced plasma levels of fatty acids such as linoleic acid, arachidonic acid, and hexadecenoic acid to levels similar to those in the normal group. A pilot study indicated that plasma levels of linoleic acid were significantly higher in lung cancer patients with EGFR mutations and identified linoleic acid as a potential biomarker for the early detection of lung cancer ( 21 ). Lung tumor cell survival can be inhibited by blocking arachidonic acid metabolism; thus, targeting arachidonic acid action may be beneficial for cancer therapy ( 22 ).…”
Section: Discussionmentioning
confidence: 99%